2017
DOI: 10.4103/2153-3539.201920
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study Comparing Digital Imaging to Traditional Glass Slide Microscopy for Breast Biopsy and Cancer Diagnosis

Abstract: Background:Digital whole slide imaging may be useful for obtaining second opinions and is used in many countries. However, the U.S. Food and Drug Administration requires verification studies.Methods:Pathologists were randomized to interpret one of four sets of breast biopsy cases during two phases, separated by ≥9 months, using glass slides or digital format (sixty cases per set, one slide per case, n = 240 cases). Accuracy was assessed by comparing interpretations to a consensus reference standard. Intraobser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…It is worth noting that variation in the number of ROIs across cases was not correlated with reference case difficulty. Furthermore, expert interpretations of these 24 cases were highly concordant (21/24 cases) between the digital and glass versions (for a more in depth examination of this issue, see 36 ).…”
Section: Methodsmentioning
confidence: 88%
“…It is worth noting that variation in the number of ROIs across cases was not correlated with reference case difficulty. Furthermore, expert interpretations of these 24 cases were highly concordant (21/24 cases) between the digital and glass versions (for a more in depth examination of this issue, see 36 ).…”
Section: Methodsmentioning
confidence: 88%
“…Our previous studies found that accuracy was slightly higher when pathologists used glass slides, as the current study did, compared to digital whole slide imaging (WSI), an emerging technology for pathology interpretation. 18,23 Although currently understudied, intra-observer variability also has the potential to be greater using WSI.…”
Section: Discussionmentioning
confidence: 99%
“…Whole slide imaging (WSI), also known as virtual microscopy, is the transformation of glass slides of the tissue section to digital images by WSI scanners which are run with computer workstations and specific software . WSI has various pragmatic uses such as diagnosis, education, research, and telepathology consultation .…”
Section: Introductionmentioning
confidence: 99%
“…Another dynamic use of WSI results in promotion of the workflow by avoiding the extra‐work of slide allocation . The swift increase of improvements in this field and their various advantages may lead to a change from light microscopy to digital pathology for routine pathological diagnosis . At present there are many WSI scanners, related workstations and specific software available that are capable of performing good quality digitalization …”
Section: Introductionmentioning
confidence: 99%